Asplenium atlanticum (Aspleniaceae), a new endemic fern from the Brazilian Atlantic Forest - Lino, Vanessa; Reis, Atiles; Da Silva Sylvestre, Lana; Massi Mynssen, Claudine (Phytotaxa, 2023)
Asplenium atlanticum (Aspleniaceae), a new species from the Atlantic Forest of Brazil, is described and compared to similar species. It is morphologically related to Asplenium martianum, from which it differs by having deltoid to lanceolate laminae, ovate pinnules with an obtuse apex, elliptic and linear sori, and longer stem scales. It is also similar to Asplenium muellerianum, from which it differs by having longer stem scales, deltoid to lanceolate laminae, and pinnae with an obtuse to acute apex, and to Asplenium pseudonitidum, from which it differs by having shorter and dull petiole, laminae with dentate margins, and pinnules always with obtuse apex. Asplenium atlanticum is known from Paraná, Rio Grande do Sul, and Santa Catarina states. The new species is illustrated, and an identification key to its closely related species is provided.